2022
DOI: 10.1038/s41467-022-29202-x
|View full text |Cite
|
Sign up to set email alerts
|

Guide RNAs containing universal bases enable Cas9/Cas12a recognition of polymorphic sequences

Abstract: CRISPR/Cas complexes enable precise gene editing in a wide variety of organisms. While the rigid identification of DNA sequences by these systems minimizes the potential for off-target effects, it consequently poses a problem for the recognition of sequences containing naturally occurring polymorphisms. The presence of genetic variance such as single nucleotide polymorphisms (SNPs) in a gene sequence can compromise the on-target activity of CRISPR systems. Thus, when attempting to target multiple variants of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…For example, a recent report by Krysler et al showed how chemically synthesized crRNA with universal bases, or nucleotides with the ability to base pair with all four bases, could be used to allow RNP complexes to target genes with many singlenucleotide polymorphisms (SNPs). 34 For a multi-gene editing assay, another double-clicked sgRNA was prepared containing a Cy5-modified thymine in the tetraloop that corresponded to the Siglec-3 target. This Cy5-modified sgRNA specific for Siglec-3 and an ATTO-550-modified sgRNA specific for Siglec-7 could be independently monitored by their distinct fluorescent properties.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent report by Krysler et al showed how chemically synthesized crRNA with universal bases, or nucleotides with the ability to base pair with all four bases, could be used to allow RNP complexes to target genes with many singlenucleotide polymorphisms (SNPs). 34 For a multi-gene editing assay, another double-clicked sgRNA was prepared containing a Cy5-modified thymine in the tetraloop that corresponded to the Siglec-3 target. This Cy5-modified sgRNA specific for Siglec-3 and an ATTO-550-modified sgRNA specific for Siglec-7 could be independently monitored by their distinct fluorescent properties.…”
Section: Resultsmentioning
confidence: 99%
“…LASV, a viral pathogen and an etiologic agent of a highly lethal hemorrhagic fever (Lassa fever-LF) 18 , has always posed difficulty for the development of nucleic acid based assays due to its high variability with close to 30% divergence on the RNA level 19,20 . An alternative approach using "universal" crRNA for Cas9-based editing of polymorphic genes was shown by Krysler et al 21 That approach utilized nucleotides such as inosine (which pairs with all four RNA nucleotides). In comparison, our approach uses degenerate crRNA sets comprised of standard RNA nucleotides.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…With PECAN, pathogens with small regions of conserved regions could be detected with cas12a without the presence of a conserved PAM site, which decreases the need for degenerative or polymorphic crRNA [50]. PECAN is applicable to the detection of bacterial or viral species.…”
Section: Discussionmentioning
confidence: 99%